Accounting Information System as a Strategic Decision Making Tool in Banking Sector: Evidence from Bangladesh - Rahman, Khondoker Ziaur (Asian Business Review, 2016)
The core of any organization is accounting information, through which organizations become able to understand the financial situation of the business and they uses this accounting information from integration system as a basis for making strategic decisions. Since premeditated decisions have long term effect on the business and therefore it is important to analyze information from accounting information system for making long-term planned decisions. This study aiming to find out the impact of accounting information system as a strategic decision making tool focusing on the banking sector of Bangladesh. After conducting a questionnaire survey among 40 different private and public banks from Bangladesh, result shows that out of total respondent 72.5% are using this tool frequently on their Bank. I believe that this study will be able to find out importance of accounting information system as a strategic decision making tool in banks from developing countries. And this study will be helpful for the other developing countries banks if they are planning for implementing accounting information system as a decision making tool.